Demicryptochironomus Lenz from China (Diptera: Chironomidae) - Yan, Chuncai; Tang, Hongqu; Wang, Xinhua (Zootaxa, 2005)
The genus Demicryptochironomus Lenz 1941 from China is revised. The males of six new species are described: D. (Demicryptochironomus) antennarius sp. n., D. (D.) minus sp. n., D. (D.) pannus sp. n., D. (D.) yui sp. n., D. (Irmakia) concavus sp. n., D. (I.) constrictus sp. n. Demicryptochironomus (I.) neglectus Reiss 1988 is new to China. Demicryptochironomus (D.) vulneratus (Zetterstedt 1838) and D. (I.) spatulatus Wang & Zheng 1994 are redescribed. The larva of D. (D.) vulneratus is described from China for the first time, and an unplaced larva is described. Keys to males and known larvae of the genus are presented. An emended generic diagnosis is given and the systematics discussed.